A critical review of the state of the art literature in the monitoring of ultrasonic machining process and tool failure prediction. (December 2021) - Mirad, Mehdi Mehtab; Das, Bipul
Highlights: Effects of process parameters in ultrasonic machining are summarized. Condition monitoring approaches in USM is reviewed. Tool failure assessment methods are reviewed. Future research possibilities and opportunities are presented. Abstract: Ultrasonic machining (USM) is an unconventional machining process. It is mainly used for material removal from the brittle and hard workpiece by using a high-frequency longitudinal mode of vibration. There are several process parameters are used in the ultrasonic machining to achieve the outcomes like tool wear rate, surface roughness, material removal rate, hole quality, and conicity. Tool wear is the most unwanted occurrence of the machining process as it unpleasantly affects the tool life, surface finish of the machined surface, and its dimensional precision. The destructive and non-destructive methods can be used for quality assessment and defect identification during machining. However, these methods suffer from limitations as their high setup and operating cost. Alternatively, condition monitoring can be used to monitor the machining quality and defect identification in the ultrasonic machining process.